Environmental Growth Response of Gracilaria sp. under Two Water-Medium Ratios for Aquatic Biofiltration - Henokh Wau; Aulia Ulfah Farahdiba (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Environmental conditions regulate macroalgal growth and determine whether living biomass can function as an aquatic biofilter. This preliminary study described changes between day 0 (D0) and day 7 (D7) in one best final-weight culture unit selected from each of two water-medium ratios: P1 (1:0) and P2 (1:1). Wet weight, pH, temperature, salinity, dissolved oxygen (DO), and nitrate concentration were evaluated. Wet weight increased from 100.0 to 105.0 g in the 1:0 unit (+5.0%; specific growth rate 0.70% day?¹) and to 105.1 g in the 1:1 unit (+5.1%; 0.71% day?¹). In the 1:0 unit, pH rose from 7.14 to 7.44, temperature from 26.4 to 28.9 °C, salinity from 40.9 to 42.0 ppt, and DO remained at 5 mg L?¹. In the 1:1 unit, pH rose from 7.22 to 7.43 and temperature from 26.4 to 29.1 °C, while salinity declined from 42.0 to 38.3 ppt and DO from 6 to 5 mg L?¹. Nitrate concentration decreased from 9.62 to 0.00 mg L?¹ in the 1:0 unit and from 8.58 mg L?¹ to not detected (ND) in the 1:1 unit. Both selected units maintained positive short-term growth under different environmental trajectories, supporting the preliminary feasibility of Gracilaria sp. as a biofilter component. Because deliberately selected single units were analyzed and nitrate was the only nutrient parameter quantified, the findings do not establish ratio superiority or comprehensive biofiltration efficiency. Replicated trials with direct nutrient mass balances are required. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water